2018
DOI: 10.1080/10508406.2018.1522258
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding Student Understanding in Small-Group Work: Students’ Uptake of Teacher Support in Subsequent Small-Group Interaction

Abstract: Providing contingent or adaptive support (i.e., scaffolding) is effective. Yet it is unclear how it promotes students' learning. In this mixed-methods study, we investigated to what extent the effect of contingent support for students' learning is mediated by the extent to which students take up teachers' support in subsequent small-group work. We define contingent support as support that contains adapted levels of teacher control or regulation based on the learner's level of understanding. To explore the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 37 publications
2
49
1
12
Order By: Relevance
“…Mitchell and Vidal (2001) and Richards and Rogers (2001) believe that approaches and methods in second language teaching have both dynamics and diversity. In other words, advancements in socio-cultural theory (Van Boxtel, Van der Linden, & Kanselaar, 2000;Van de Pol, Mercer, & Volman, 2019), educationalpsychological theory (VanPatten; Vallori, 2014;Wittwer & Renkl, 2008), neuroscience (Benati & Rastelli, 2018;), and technological advancements (Brown, 2009;Hartman, Townsend, & Jackson, 2019;Leutner, 2019;Rassaei, 2018) have made changes to human perceptions and conceptions of effective second language teaching. These advancements, eventually, turn into innovations in research and practices in second language teaching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell and Vidal (2001) and Richards and Rogers (2001) believe that approaches and methods in second language teaching have both dynamics and diversity. In other words, advancements in socio-cultural theory (Van Boxtel, Van der Linden, & Kanselaar, 2000;Van de Pol, Mercer, & Volman, 2019), educationalpsychological theory (VanPatten; Vallori, 2014;Wittwer & Renkl, 2008), neuroscience (Benati & Rastelli, 2018;), and technological advancements (Brown, 2009;Hartman, Townsend, & Jackson, 2019;Leutner, 2019;Rassaei, 2018) have made changes to human perceptions and conceptions of effective second language teaching. These advancements, eventually, turn into innovations in research and practices in second language teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Updates in second language teaching in the post-methods era have added teaching techniques that teachers should follow. Taking part in these tasks and activities, teachers can vary students' interaction patterns that facilitate a communicative environment for learners (Van de Pol, Mercer, & Volman, 2019). Teachers should also provide learning strategies to help learners become more confident and increase their autonomy (Almusharraf, 2018;Smith, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To establish that the two groups of students were comparable at the outset of the intervention, we compared three of the major pre-test measures drawn from the larger project: (1) peer acceptance, defined as the extent to which peers like to work and play with each student, was assessed using a peer nomination approach in which students rated each of their classmates according to how much they liked to play or work with that peer on a scale of 1 (not at all) to 10 (very much) (Parker and Asher, 1993); (2) social reasoning, defined as knowledge about the complex social world (Turiel, 1983), was assessed by an individual essay task, which was coded based on a coding scheme designed to examine the number of perspectives students considered in the essay (see Kraatz et al, 2019 for more details about the coding scheme; inter-rater reliability α = 0.88); (3) academic achievement, which was based on students' 4th grade state standardized language arts scores. Independent samples t-tests were conducted to compare the groups' average peer acceptance, social reasoning, and academic performance.…”
Section: Case Selectionmentioning
confidence: 99%
“…The effectiveness of scaffolding is dependent on various factors such as contingency (appropriateness of support based on student needs/ability), context, timing of fading, and nature of the task ( Howe, 2013 ; van de Pol et al, 2015 , 2019 ). van de Pol et al (2015) showed that a combination of the above-mentioned factors together influences student outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation